2004
DOI: 10.1126/science.1097931
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Mammalian Midbody Proteome Reveals Conserved Cytokinesis Mechanisms

Abstract: Cytokinesis is the essential process that partitions cellular contents into daughter cells. To identify and characterize cytokinesis proteins rapidly, we used a functional proteomic and comparative genomic strategy. Midbodies were isolated from mammalian cells, proteins were identified by multidimensional protein identification technology (MudPIT), and protein function was assessed in Caenorhabditis elegans. Of 172 homologs disrupted by RNA interference, 58% displayed defects in cleavage furrow formation or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
519
2
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(557 citation statements)
references
References 70 publications
(51 reference statements)
31
519
2
5
Order By: Relevance
“…Because each tandem mass spectrum represents an independent and verifiable piece of data, this approach to database searching has the ability to identify proteins in mixtures, enabling a rapid and comprehensive approach for the analysis of protein complexes and other complicated mixtures of proteins 6,[8][9][10][11][12] . New biology has been discovered based on fast and accurate protein identification [13][14][15][16][17][18] . As tandem mass spectral protein identification has proliferated, it has become increasingly important to understand the rationale of individual database search algorithms, their relative strengths and weaknesses, and the mathematics used to match sequence to spectrum.…”
mentioning
confidence: 99%
“…Because each tandem mass spectrum represents an independent and verifiable piece of data, this approach to database searching has the ability to identify proteins in mixtures, enabling a rapid and comprehensive approach for the analysis of protein complexes and other complicated mixtures of proteins 6,[8][9][10][11][12] . New biology has been discovered based on fast and accurate protein identification [13][14][15][16][17][18] . As tandem mass spectral protein identification has proliferated, it has become increasingly important to understand the rationale of individual database search algorithms, their relative strengths and weaknesses, and the mathematics used to match sequence to spectrum.…”
mentioning
confidence: 99%
“…Une hypothèse particulièrement intéressante serait que p27 soit capable de cibler des complexes cycline/CDK vers des protéines spécifiques du midbody (comme citron-K) ou puisse inhiber l'activité de ces complexes au midbody, à un moment donné, pour réguler le processus d'abscission. De manière intéressante, lors d'un criblage protéomique réalisé afin d'identifier les protéines présentes au midbody, CDK1 et CDK4 ont effectivement été trouvées [11]. Reste à comprendre le rôle en culture [10].…”
Section: Magnesium Transporter Protein 1 a New Intermediate In Tcr Sunclassified
“…There is very little information on the application of MudPIT in cancer research. It was reported that this technology has been successfully applied to study cytokinesis proteins, consensus mammalian mediator subunits, and membrane and soluble proteins [49][50][51]. While the older generation instruments used for Mud-PIT were not suitable for quantitative proteomics, the introduction of DeCyder MS software (GE Healthcare), and the multidimensional LC (MDLC, GE-Healthcare) which incorporates advanced LC systems and can be coupled to new MS instruments, e.g., the LTQ (Thermo-Finnegan) may position the MudPIT as a key label-free proteomic technology in the near future.…”
Section: Multi-dimensional Protein Identification Technology (Mudpit)mentioning
confidence: 99%